Neuroretina specification in mouse embryos requires Six3-mediated suppression of Wnt8b in the anterior neural plate - Liu, Wei; Lagutin, Oleg; Swindell, Eric; Jamrich, Milan; Oliver, Guillermo (The Journal of Clinical Investigation, 2010)
Retinal degeneration causes vision impairment and blindness in humans. If one day we are to harness the potential of stem cell–based cell replacement therapies to treat these conditions, it is imperative that we better understand normal retina development. Currently, the genes and mechanisms that regulate the specification of the neuroretina during vertebrate eye development remain unknown. Here, we identify sine oculis–related homeobox 3 (Six3) as a crucial player in this process in mice. In Six3 conditional–mutant mouse embryos, specification of the neuroretina was abrogated, but that of the retinal pigmented epithelium was normal. Conditional deletion of Six3 did not affect the initial development of the optic vesicle but did arrest subsequent neuroretina specification. Ectopic rostral expansion of Wnt8b expression was the major response to Six3 deletion and the leading cause for the specific lack of neuroretina, as ectopic Wnt8b expression in transgenic embryos was sufficient to suppress neuroretina specification. Using chromatin immunoprecipitation assays, we identified Six3-responsive elements in the Wnt8b locus and demonstrated that Six3 directly repressed Wnt8b expression in vivo. Our findings provide a molecular framework to the program leading to neuroretina differentiation and may be relevant for the development of novel strategies aimed at characterizing and eventually treating different abnormalities in eye formation.